Get Answers to all your Questions

header-bg qa

  Put into another form using a^{m}\times b^{m}= (ab)^{m} :

            (i)\: 4^{3}\times 2^{3}         (ii)\: 2^{5}\times b^{5}     (iii)\: a^{2}\times t^{2}     (iv)\: 5^{6}\times (-2)^{6}     (v)\: (-2)^{4}\times (-3)^{4}

 

Answers (1)

best_answer

 (i)\: 4^{3}\times 2^{3}     

can be simplified as  (4\times 2)^3=8^3

(ii)\: 2^{5}\times b^{5}    

can be simplified as (2\times b)^5=(2b)^5

(iii)\: a^{2}\times t^{2}

can be simplified as     (a\times t)^2=at^2

(iv)\: 5^{6}\times (-2)^{6} 

can be simplified as    (5\times (-2))^6=-10^6

(v)\: (-2)^{4}\times (-3)^{4}

can be simplified as ((-2)\times (-3))^4= 6^4

Posted by

seema garhwal

View full answer